A 33-year diagnostic odyssey in an Ashkenazi Jewish patient with Aicardi-Goutières syndrome - Oskar Schnappauf, PhD; Hongying Wang, PhD; Ivona Aksentijevich, MD; Daniel L. Kastner, MD, PhD; Ronald M. Laxer, MD (Journal of Allergy and Clinical Immunology: Global)
The critical need for awareness and genetic testing of the SAMHD1 deletion in Ashkenazi Jewish patients is highlighted owing to its relatively high carrier frequency. Early detection can prevent severe disease complications through targeted therapy.